Osobennosti formirovanija sorevnovatel'noj gotovnosti rossijskich dzjudoistov k vystuplenijam na meždunarodnoj arene - Adolf, V. A.; Sidorov, L. K.; Kudryavtsev, M. D.; Osipov, A. Y.; Bliznevsky, A. Y. (Teorija i Praktika fiziceskoj Kul'tury, 2018)
The study analyzes the precompetitive fitness methods applied by the Russian judo teams prior to the top-ranking international events to secure due competitiveness and performance quality for the athletes. Sampled for the study were the competitive bouts of 74 elite Russian judo competitors from regional/ territorial picked teams. Subject to analysis under the study were the video captures of competitive bouts with the individual performances rated by experts. The expert analysis of the competitive bouts found the following drawbacks in the fight techniques and tactics: (1) Low activity in the ground (Ne-waza) positions, with most of the fighters prone to use the ground positions for keeping the lead i.e. fighting against time rather than active offence; (2) Low success rate of the offense in standing (Nage-waza) positions; and (3) Low activity in the competitive bouts, with experts particularly unhappy with the long (40+ second) time gaps between the technical actions of the sampled athletes. In view of the increasingly biased refereeing of the bouts of Russian competitors, the national judo community shall give a special priority to active offence and determined and frequent technical actions for success.